2014
DOI: 10.1152/japplphysiol.00584.2014
|View full text |Cite
|
Sign up to set email alerts
|

Systemic stiffening of mouse tail tendon is related to dietary advanced glycation end products but not high-fat diet or cholesterol

Abstract: Tendon pathology is related to metabolic disease and mechanical overloading, but the effect of metabolic disease on tendon mechanics is unknown. This study investigated the effect of diet and apolipoprotein E deficiency (ApoE(-/-)) on mechanical properties and advanced glycation end product (AGE) cross-linking of non-weight-bearing mouse tail tendons. Twenty ApoE(-/-) male mice were used as a model for hypercholesterolemia along with 26 wild-type (WT) mice. One-half of the mice from each group was fed a normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
6
27
1
Order By: Relevance
“…When CML is used as a marker of endogenous advanced glycation in preclinical studies, it is therefore essential to measure the level of dCML in the chow and to distinguish free from protein‐bound CML. The dCML content in the ND used here was similar to that found by other workers . We also found that the two DIO diets had six to seven times less dCML than the ND (idem carboxyethyllysine; data not shown), despite a higher lysine content.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When CML is used as a marker of endogenous advanced glycation in preclinical studies, it is therefore essential to measure the level of dCML in the chow and to distinguish free from protein‐bound CML. The dCML content in the ND used here was similar to that found by other workers . We also found that the two DIO diets had six to seven times less dCML than the ND (idem carboxyethyllysine; data not shown), despite a higher lysine content.…”
Section: Discussionsupporting
confidence: 90%
“…Among the DIO models, the lower dCML exposure for the HFD and HF‐HSD mice was reflected in the lower free CML concentration found in kidneys and lungs compared with ND mice. This association between relatively low exposure to dCML via an HFD and a low total CML content in vivo has been observed by others in the tail tendon of mice . Without excluding other potential factors for the variation of free CML in organs, our study underlines the importance of characterizing the dCML exposure and, more particularly, of analytically distinguishing free from protein‐bound CML.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Training compliance was not statistically different for men (old: 74 Ϯ 6; very old: 92 Ϯ 4) and women (old: 67 Ϯ 9; very old: 85 Ϯ 13). Finally, although training did not affect old or very old individuals differently, we cannot exclude that the different nutritional supplementation in old and very old individuals may have affected the training response, since whey protein seems to augment tendon hypertrophy in young men (23), and diet generally seems to influence tendon composition and mechanics in animals (22,56,60). The possible influence of different nutritional supplementations on improvements in muscle strength and cross-sectional area is less relevant to the present investigation, since we compared tendon mechanical properties at the two time points at common force level.…”
Section: Limitationsmentioning
confidence: 87%
“…At the molecular level, the mechanisms driving diabetic tendinopathy are unclear. However, several studies have suggested that Advanced Glycation Endproducts (AGEs), which are dramatically increased in T2DM tissue (22), may promote loss of collagen organization due to altered cross-linking resulting from AGEcollagen binding (23). However, Fessel et al, have recently demonstrated that AGEs are unable to induce tissue level impairments in tendon mechanical properties (24), suggesting other mechanisms may be driving this phenotype.…”
Section: Discussionmentioning
confidence: 99%